Association between frequency of breakfast consumption and cardiometabolic risk in Peruvian university teachers, 2019–2020 - Jacksaint Saintila; Laura E. Baquedano-Santana; Yaquelin E. Calizaya-Milla; Cristian Ramos-Vera; Antonio Serpa Barrientos; Renzo F. Carranza-Esteban (Frontiers in Nutrition, 2023)
BackgroundAlthough the relationship between health status and dietary intake has been extensively studied in the general population, there is a lack of research that has specifically examined the association between frequency of breakfast consumption and cardiometabolic risk in university teachers.ObjectiveTo determine the association between the frequency of breakfast consumption and cardiometabolic risk in university teachers.MethodsA cross-sectional study was conducted in 176 teachers from a private university located in the eastern region of Lima, Peru (Mage: 37.0 years; SD: 0.8, range: 24–59 years). The study was conducted during the period from December 2019 to February 2020. Information was collected on anthropometric and biochemical parameters and frequency of breakfast consumption. Multinomial logistic regression models were used to explore the association between frequency of breakfast with sociodemographic, anthropometric, and biochemical variables.ResultsThe highest prevalence of excess body weight (44.4%) was observed in those who consumed breakfast 0 to 2 days/week, but without statistical differences. Those who reported Low-density lipoprotein cholesterol (LDL-C) < 160 mg/dL were 77% less likely to fall into the 3–5 day/week breakfast frequency category than those who reported a regular frequency of breakfast (6 to 7 days/week) (Adjusted OR = 0.23, 95% CI 0.08 to 0.73; p < 0.05). In addition, teachers who reported a breakfast frequency of 3 to 5 days/week were 83% more likely to have a glucose concentration < 110 mg/dL compared to those who consumed breakfast of 6 to 7 days/week (Adjusted OR = 0.17, 95% CI 0.04 to 0.75; p < 0.05).ConclusionSkipping breakfast for an extended period of time can have detrimental effects on cardiometabolic health. Promoting the benefits of breakfast could be a health message of great public health interest.